Ondel-Ondel Betawi E-Book for Early Childhood Anti-Corruption Education - Agita Violy (Southeast Asian Journal on Open and Distance Learning, 2024)
Anti-corruption education for early childhood is crucial in fostering an integrity-driven generation. This study examines the use of Betawi Ondel-Ondel stories to convey anti-corruption values to young children. Unlike previous research that often employed conventional character education methods, this study focuses on utilizing local cultural elements as an innovative learning approach. The research aims to evaluate the potential of Ondel-Ondel stories in teaching values such as honesty and justice, integrating these principles into daily learning activities. The motivation behind this research is to connect character education with engaging cultural aspects relevant to children. The methodology includes literature review, symbolic analysis of Ondel-Ondel, and observations and interviews with educators. Findings indicate that the Ondel-Ondel character significantly enhances children's understanding of the importance of honesty and justice. Policy implications suggest the need to incorporate local cultural elements into the anti-corruption education curriculum to make learning materials more engaging and relevant. This study aims to assist educators and policymakers in designing innovative and impactful teaching methods.